2016
DOI: 10.1128/jvi.02666-15
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Mechanistic, and Antigenic Characterization of the Human Astrovirus Capsid

Abstract: Human astroviruses (HAstVs) are nonenveloped, positive-sense, single-stranded RNA viruses that are a leading cause of viral gastroenteritis. HAstV particles display T=3 icosahedral symmetry formed by 180 copies of the capsid protein (CP), which undergoes proteolytic maturation to generate infectious HAstV particles. Little is known about the molecular features that govern HAstV particle assembly, maturation, infectivity, and immunogenicity. Here we report the crystal structures of the two main structural domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…To determine if MAb PL-2 binds to the HAstV-2 CP spike (Spike2), the outermost domain on the virus surface, we first produced and purified recombinant Spike2 and observed that it elutes as a dimer by size exclusion chromatography, consistent with previous observations for Spike1 and Spike8 (26,27). To further show that Spike2 is folded correctly, we determined its structure to 1.87 Å ( Fig.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…To determine if MAb PL-2 binds to the HAstV-2 CP spike (Spike2), the outermost domain on the virus surface, we first produced and purified recombinant Spike2 and observed that it elutes as a dimer by size exclusion chromatography, consistent with previous observations for Spike1 and Spike8 (26,27). To further show that Spike2 is folded correctly, we determined its structure to 1.87 Å ( Fig.…”
Section: Resultssupporting
confidence: 69%
“…While the immature Tϭ3 HAstV particle contains 90 dimeric spikes, trypsin proteolysis leaves the mature Tϭ3 HAstV particle with only 30 dimeric spikes located on the 2-fold icosahedral axes. Our lab and others have determined the structures of the dimeric CP spikes from HAstV-1, HAstV-8, and turkey astrovirus 2 (26)(27)(28). We also reported the structure of the HAstV CP core domain that forms the icosahedral shell (26).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…A search for structures similar to the DWV P domain (22) identified a globular surface domain of a virus from the Astroviridae, an additional family of nonenveloped viruses like the picornaviruses and caliciviruses, all of which possess a single-stranded positive sense RNA genome (Table S2) (23). The domain is similar to the P domain of DWV in terms of having a core formed by β-strands that are complemented by short α-helices located at the periphery of the domain.…”
Section: Resultsmentioning
confidence: 99%